1977
DOI: 10.2307/1936218
|View full text |Cite
|
Sign up to set email alerts
|

The Relationships of Locomotion to Differential Predation on Pseudacris Triseriata (Anura: Hylidae)

Abstract: Laboratory experiments, using the garter snake Thamnophis sirtalis as predator and the chorus frog Pseudacris triseriata as prey, show that metamorphosing anurans are captured more frequently by T. sirtalis than either premetamorphic tadpoles or postmetamorphic frogs. Stomach contents of wild-caught Thamnophis have similarly revealed more anuran prey in transformation than at earlier or later stages. The high susceptibility of transforming Pseudacris to snake predation appears to be a direct consequence of a b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
202
3
1

Year Published

1988
1988
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 225 publications
(211 citation statements)
references
References 17 publications
5
202
3
1
Order By: Relevance
“…Several other studies have also reported an increase in swimming velocity with increases in total length in premetamorphic tadpoles (Wassersug and Sperry 1977;Huey 1980;Wassersug and Hoff 1985;Brown and Taylor 1995;Parichy and Kaplan 1995). Huey (1980) found average swimming velocity in tadpoles of Bufo boreas positively correlated with tail length between stages 31 and 41.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Several other studies have also reported an increase in swimming velocity with increases in total length in premetamorphic tadpoles (Wassersug and Sperry 1977;Huey 1980;Wassersug and Hoff 1985;Brown and Taylor 1995;Parichy and Kaplan 1995). Huey (1980) found average swimming velocity in tadpoles of Bufo boreas positively correlated with tail length between stages 31 and 41.…”
Section: Discussionmentioning
confidence: 81%
“…In an unpublished study, Hoff (1987) reported that length-specific swimming velocities of anuran larvae generally decreased with increasing body length; however, scaling relationships differed between species, with the length-specific swimming velocity of at least one species of anuran larvae (Xenopus laevis) showing no influence of total length. Most locomotor studies of anuran tadpoles have concentrated more on the influence of ontogenetic changes in body shape and the consequences of their globose body shape rather than body-size effects on swimming performance (Wassersug and Sperry 1977;Huey 1980;Wassersug and Hoff 1985;Wassersug 1989;Brown and Taylor 1995;Liu et al 1996Liu et al , 1997.…”
Section: Introductionmentioning
confidence: 99%
“…I that large tadpoles have significantly lower critical velocities than small tadpoles (Table 4.7). In Expt.I, mass was tightly correlated with developmental stage so it is unclear whether bigger tadpoles had poor performance maintaining position in the interstitial spaces among the rocks in the Brett chamber by virtue of their size, or because of morphological changes such as large hind limbs which can increase frontal drag on a stationary tadpole and decrease swimming performance (Dudley et al 1991, Wassersug andSperry 1977). In addition to the obvious external changes, later stages have internal changes including the development of lungs which affect buoyancy and hardwired neurological behaviors such as surfacing to reinflate lungs periodically in response to increasing CO2 concentrations (Gdovin et al 2006).…”
Section: Brett Chamber Critical Velocity Results and Discussionmentioning
confidence: 99%
“…On the contrary, it might produce the worst performance. For example, metamorphosing tadpoles are most vulnerable to predators during the developmental transition (with legs and a tail) due to their worst escape performance (Wassersug and Sperry 1977;Crump 1984). Similarly, in horned beetles, intermediate morphologies are rare or absent from natural populations due to their inferior competition for mating (Madewell and Moczek 2006).…”
Section: Discussionmentioning
confidence: 99%